Microwave System: A Novel Treatment for Localized Adiposity Reduction in a Latin American Population - Aura Ibeth Ruiz-Rosas; Nelly Patricia Muño-Velasco; Dayana Sofia Rengifo-Bolaños; Tatiana Carolina Reyes-Vivas; Paula Lozano-Bitar; Irene Fusco; Paola Andrea Russy-Buitrago (Journal of Nutrition and Metabolism)
Background. The microwave body remodeling system is indicated for people who want to improve their physical appearance as it can penetrate deep tissues, causing thermic stress on adipocytes to produce adipolysis while in superficial tissues, it dissolves fibrous tracts and stimulates new collagen. Objectives. The aim of this study was to assess the localized adiposity reduction in Latin American patients using a microwave system. Methods. A total of 35 patients with a mean age of 47.5 (±9.0) years received body remodeling treatment, using the microwave system between the years 2019–2022 in a Bogota, Colombia reference center. Data descriptive analysis was made as well as single-factor repeated measures ANOVA to show pre- and post-treatment difference, and mixed ANOVA for body mass index (BMI) subgroup analysis was performed. Results. In all patients examined, statistical significant differences were found in pre- and post-treatment skinfold test for each body area: superior abdomen (F(1,27) = 63.13; p=0.001), iliac crest (F(1, 23) = 114.33; p<0.001), posterior waist (F(1, 20) = 27.36; p<0.001), trochanter (F(1, 17) = 26.94; p<0.001), among others. Conclusions. According to the study’s findings, this microwave system is an innovative and effective technique for body remodeling and cellulite and localized fat reduction.